Shifts in hospital-associated pathogens and prevalence trends of carbapenem-resistant Escherichia coli infections, 2021–2023 - Luyao Liu; Shihui Liu; Zhenghai Yang; Fan Wang; Huiwen Yuan; Hao Xu; Jinguan Chen; Xiaoning Li (Journal of Infection in Developing Countries)
Introduction: Carbapenem-resistant Escherichia coli (CREC) have emerged as a significant global health threat, particularly in hospital settings, due to their high resistance to critical antibiotics. This study aimed to evaluate the dynamics of pathogenic bacterial isolates in clinical specimens, characterize patients with CREC infections, and identify risk factors for co-infection; in order to strengthen surveillance and infection control measures.